ANTI-MOSQUITO PROPERTIES OF METHANOL EXTRACT OF Clerodendrum polycephalum Baker (2018)
ABSTRACT Mosquitoes are vectors of various diseases of public health importance and their control has been premised on the use of synthetic insecticides. However, these insecticides are laden with problems of high cost, environmental hazards and development of resistance in many species of mosquitoes. Alternatives to synthetic substances are the natural products. Plant species, Clerodendrum inerme, have been found to inhibit the growth of Aedes aegypti and Culex quinquefasciatus larvae. However, there is paucity of information on the anti-mosquito properties of the Nigerian species, C. polycephalum Baker. Therefore, the aim of the study was to investigate the anti-mosquito properties of the methanol extract of the leaves of C. polycephalum. Fresh leaves (1.4 kg) of C. polycephalum were harvested and brought to the laboratory. The leaves were air-dried, powdered, extracted with methanol and concentrated to dryness using rotary evaporator. The crude methanol extract was subjected to phytochemical analysis according to standard method and separated into n-hexane, dichloromethane, ethyl acetate and ethanol fractions using vacuum liquid chromatography. The most active fraction (ethanol), was subjected to column chromatography. Gas Chromatography - Mass Spectroscopy (GC-MS) was used to analyse the subfraction which was ultra-violet active. The crude methanol extract and fractions (250–8000 ppm) were tested for larvicidal activity. The methanol extract was further tested for anti-oviposition, effects on growth and development on Aedes aegypti, Anopheles gambiae and Culex quinquefasciatus mosquitoes together with corresponding positive (lambda-cyhalothrin) and negative controls (dimethylsulfoxide) using World Health Organisation procedures. Toxic effects, determined by mortality, on representative non-target organisms was evaluated on adult Biomphalaria glabrata (snail) and tadpoles of Bufo regularis. Ten each of the organisms were used per concentration. Data were analysed using descriptive statistics and student’s t-test at α0.05. Tannins, flavonoids, saponins and alkaloids were identified from the crude extract. Seventeen compounds were detected from ethanol subfraction, with quantities varying from 0.0 to 23.7%. Prominent compounds include 4-((1E)-3-Hydroxy-1-propenyl)-2-methoxyphenol (7.5%), 2-Hydroxy-5-methylbenzaldehyde (6.1%) and Ethyl iso-allocholate (23.7%). Larvicidal activities of crude methanol extract and fractions were in the order ethanol (100.0%) > methanol (96.6%) > n-hexane (7.5%) > DCM/ethyl-acetate (0.0%) at 2000ppm after 24h. Susceptibilities of mosquito larvae to methanol extract were also in the order A. aegypti > A. gambiae > C. quinquefasciatus. Mortality of the larvae was significantly different from the positive control. Anti-oviposition index increased (46.4-89.9) with extract concentrations. Morphological deformities of larvae and pupae were observed at the higher doses of 2000 ppm (A. aegypti), 5000 ppm (A. gambiae) and 7000 ppm (C. quinquefasciatus). Mosquito adult emergence inhibitions (24.0-100.0%) were recorded at 1100–5600 ppm concentration levels. The crude extract had no effect on the tadpoles at 250–1000 ppm, but the mortality of the snail at 250–2000ppm, varied from 10.0–95.0%. Clerodendrum polycephalum leaves contained biological components capable of inhibiting the survival and development of mosquitoes and could be exploited in the control of mosquitoes.